ChemInform Abstract: Chemoselective Cleavage of P‐Methoxybenzyl and 2‐Naphthylmethyl Ethers Using a Catalytic Amount of HCl in Hexafluoro‐2‐propanol. Issue 5 (January 2016) - Volbeda, Anne Geert; Kistemaker, Hans A. V.; Overkleeft, Herman S.; van der Marel, Gijsbert A.; Filippov, Dmitri V.; Codee, Jeroen D. C.
Abstract: Using the title reagent, fully protected gluco‐ and mannopyranosides can be selectively Pmb‐ and naphthylmethyl‐cleaved leaving arylthio, methyl‐, benzyl‐, and silyl‐ether functions as well as acetate protective groups unaffected.